2011
DOI: 10.1158/0008-5472.can-10-3490
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 as a Biomarker for the Therapeutic Efficacy of Double-stranded RNA in Breast Cancer

Abstract: The discovery of a targeted therapeutic compound along with its companion predictive biomarker is a major goal of clinical development for a personalized anticancer therapy to date. Here we present evidence of the predictive value of TLR3 expression by tumor cells for the efficacy of Poly (A:U) dsRNA in 194 breast cancer patients enrolled in a randomized clinical trial. Adjuvant treatment with double-stranded RNA (dsRNA) was associated with a significant decrease in the risk of metastatic relapse in TLR3 posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 30 publications
7
110
1
Order By: Relevance
“…TLR3 is often expressed in murine and human tumor cells (50,51). TLR3 levels in tumor cells would be a biomarker for the therapeutic efficacy of dsRNA therapy in renal cell carcinoma and breast cancer (52,53). We found that tumor necroptosis by TLR3 signaling occurred only under specific conditions, in line with the findings that caspase-8 deficiency, caspase inhibition by zVAD, or the presence of anticaspase viral proteins is required for necroptosis induced by TNFa or death receptors (54,55).…”
Section: Discussionsupporting
confidence: 80%
“…TLR3 is often expressed in murine and human tumor cells (50,51). TLR3 levels in tumor cells would be a biomarker for the therapeutic efficacy of dsRNA therapy in renal cell carcinoma and breast cancer (52,53). We found that tumor necroptosis by TLR3 signaling occurred only under specific conditions, in line with the findings that caspase-8 deficiency, caspase inhibition by zVAD, or the presence of anticaspase viral proteins is required for necroptosis induced by TNFa or death receptors (54,55).…”
Section: Discussionsupporting
confidence: 80%
“…[5][6][7] Related to this proapoptotic function, we also found that TLR3 expressed by breast cancer cells is a biomarker for the therapeutic efficacy of dsRNA. 8 Unlike classical death receptors (DRs), TLR3 lacks a death domain (DD) and thus the molecular basis of dsRNA-triggered apoptosis through caspase-8 remains an open question although recent reports indicate that TRIF and RIP1 are required for Poly(I:C) to engage the apoptotic machinery. 5,9,10 Earlier experiments already suggested that a TRIF/RIP1/ caspase-8 complex may have some relevance as ectopic transfection of TRIF induced its binding RIP1 through its C-terminal RIP homotypic interaction motif (RHIM) 11 but also triggered apoptosis in a caspase-8-dependent manner.…”
mentioning
confidence: 99%
“…This was established by immunohistochemistry on tumor tissue sections of breast carcinoma [25], oral squamous cell carcinoma [26], cervical carcinoma [27], ovarian carcinoma [28], prostate carcinoma, head and neck carcinoma [29]. Furthermore, the level of TLR3 expression by prostate cancer cells was shown to be significantly associated with higher probability of biochemical recurrence [30].…”
Section: Inflammatory and Proliferative Responses Of Cancer Cellsmentioning
confidence: 99%